Prevalence and correlates of anxiety and depression among cancer patients in the University of Gondar Comprehensive Specialized Hospital, Northwest Ethiopia - Firnus Berihun; Sisay Haile; Mastewal Abawa; Missaye Mulatie; Alemayehu Shimeka (Archives of Depression and Anxiety - Peertechz Publications, 2017)
Background: Depression  and  anxiety  are  two  of  the  most  commonly  experienced  psychological disorders  of  cancer  patients.  They  are  associated  with  unique  psychophysiological  side  effects  that importantly  encompass  poorer  treatment  outcomes,  increased  periods  of  hospitalization  and  higher mortality  rates.  This  problem  was  not  well  studied  in  Ethiopia.  Therefore,  the  aim  of  this  study  was  to assess  the  prevalence  of  anxiety,  depression  and  associated  factors  among  cancer  patients  in  Gondar University Hospital. Methods: A  cross-sectional  study  was  conducted  among  cancer  patients  in  Gondar  University Hospital from January to June 2016. In this study, all cancer patients who were admitted to the hospital were   taken.   An   interviewer-administered   questionnaire   containing   socio-demographic   and   clinical variables, and Hospital Anxiety and depression scale and General Health Questionnaire were employed. Data  were  analyzed  using  SPSS  version  20.  Association  of  variables  with  anxiety  and  depression  was reported with chi-square and p-value. Results: A  total  of  77  cancer  patients  were  included  in  this  study.  The  prevalence  of  anxiety  and depression were 51.00% and 58.44%, respectively. Sex, educational level, residence, and monthly income had a significant association with anxiety and depression among cancer patients. Conclusions: Anxiety and depression were prevalent among cancer patients. Sex, educational status of the patients, residence, and monthly income were found to be associated with anxiety and depression. Psychological interventions targeting females, less educated patients, rural residents, and patients with lower level of monthly income may lessen their anxiety and depression burdens, in turn, to improve their survival apart from their somatic illness.